2021
DOI: 10.4236/ojped.2021.113042
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude EEG Changes in Preterm Infants at NICU of Al-Zahraa University Hospital

Abstract: Background: With increase in the incidence of preterm birth, quality of life in premature infants who suffer from perinatal brain injury has become a major concern. Amplitude electroencephalogram has the advantages of being simple bedside monitoring for assessment of brain function and follow up in preterm neonates. Aim of Study: To evaluate the aEEG changes in preterm infants and compare it to cranial ultrasound. Patients and Methods: This was a prospective observational study conducted at the NICU of Al Zahr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…These results are not surprising, as maturity differs greatly between 22-27 and 28-31 week GA newborns in other systems as well. A study by Burdjalov et al, who used the same aEEG scoring system [11], as well as Han et al [34] and Reda et al [35], showed similar results. However, all mentioned studies had different subject inclusion criteria and aEEG monitoring periods.…”
Section: Discussionmentioning
confidence: 60%
“…These results are not surprising, as maturity differs greatly between 22-27 and 28-31 week GA newborns in other systems as well. A study by Burdjalov et al, who used the same aEEG scoring system [11], as well as Han et al [34] and Reda et al [35], showed similar results. However, all mentioned studies had different subject inclusion criteria and aEEG monitoring periods.…”
Section: Discussionmentioning
confidence: 60%
“…In the monitoring of real‐time operation data in the distribution station area, many abnormal data will affect the accuracy of monitoring. In order to reduce the impact on the power grid, it is usually treated as noise [19]. However, in the monitoring of abnormal voltage quality, abnormal data is more meaningful to the monitoring of distribution network stations than other common data.…”
Section: Monitoring and Analysis Methods Of Voltage Quality In Distri...mentioning
confidence: 99%